2000
DOI: 10.1139/g00-075
|View full text |Cite
|
Sign up to set email alerts
|

A genetic map of cucumber composed of RAPDs, RFLPs, AFLPs, and loci conditioning resistance to papaya ringspot and zucchini yellow mosaic viruses

Abstract: The watermelon strain of papaya ringspot virus (PRSV-W) and zucchini yellow mosaic virus (ZYMV) are potyviruses that cause significant disease losses in cucumber. Resistances have been identified primarily in exotic germplasm that require transfer to elite cultivated backgrounds. To select more efficiently for virus resistances, we identified molecular markers tightly linked to PRSV-W and ZYMV resistances in cucumber. We generated F6 recombinant inbred lines (RILs) from a cross between Cucumis sativus L. 'Stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…More than ten maps have been established for this species (Kennard et al 1994, Serquen et al 1997, Park et al 2000, Bradeen et al 2001, Fazio et al 2003b, Zhang et al 2004, Staub et al 2007, Yuan et al 2008a, 2008b. The colinearity among linkage groups of different maps by common markers was analyzed and the commonalities of the locations of the QTLs were also explored primarily in the work of Staub et al (2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than ten maps have been established for this species (Kennard et al 1994, Serquen et al 1997, Park et al 2000, Bradeen et al 2001, Fazio et al 2003b, Zhang et al 2004, Staub et al 2007, Yuan et al 2008a, 2008b. The colinearity among linkage groups of different maps by common markers was analyzed and the commonalities of the locations of the QTLs were also explored primarily in the work of Staub et al (2007).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several molecular linkage maps in cucumber have been constructed (Kennard et al 1994, Serquen et al 1997, Park et al 2000, Fazio et al 2003b, Zhang et al 2004 for different research objectives. In order to fulfill breeding demand in cucumber production in China, by using F 2:3 and RIL (recombinant inbred line) populations, our laboratory previously has detected QTLs for nine fruit-related traits (such as fruit weight, length, and diameter) and three flower-related traits (first flower node, first female flower node and female flower ratios) of this species (Yuan et al 2008a(Yuan et al , 2008b, from which a SCAR marker (S94A1) and an EST-SSR (simple sequence repeats derived from expression sequence tag) marker (CSEPGN11) closely linked to female sex expression (F) gene were also developed.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been several reports (Park et al 2000, Fazio et al 2003b, Sakata et al 2006 of linkage map and QTL analyses in cucumber, the majority of the markers were dominant markers such as RAPDs and AFLPs, and were thus less transferable, whereas few (10 to 14) mapped SSR markers were found in these maps. Our linkage map is thus the most comprehensive map in terms of the number of SSR markers, though we were unfortunately unable to match the seven linkage groups we expected from the chromosome number of cucumber (i.e., 2n = 14).…”
Section: Construction Of An Ssr-based Genetic Linkage Mapmentioning
confidence: 96%
“…The order of and distances between the common markers in the present study were similar to those in previous studies. In genetic linkage maps of cucumber, genes or QTLs for resistance to diseases such as scab, downy mildew, papaya ringspot virus, zucchini yellow mosaic virus, and powdery mildew have been mapped (Kennard et al 1994, Park et al 2000, Sakata et al 2006. Morphological traits such as sex expression, determinate and little leaf (Kennard et al 1994, Zheng et al 2008, Bradeen et al 2001 and horticultural traits such as days to anthesis, lateral branching, fruit number per plant, fruit length, fruit diameter and fruit weight (Fazio et al 2003b, Yuan et al 2008 were identified in cucumber maps.…”
Section: Construction Of An Ssr-based Genetic Linkage Mapmentioning
confidence: 99%
See 1 more Smart Citation